The balance : my years coaching Simone Biles - Boorman, Aimee, 1973-; Cooper, Steve (Journalist) (Abrams Press, 2025)
"From Paris Olympics star and legendary gymnast Simone Biles's longtime coach, an insider's look at the making of a champion. With a Foreword by Simone Biles. The Balance is coach Aimee Boorman's inside account of the growth of a transcendent athlete and the tumultuous events--from the dictatorial coaching of Martha Karolyi to the sexual abuse by Larry Nassar--that upended the lives of many girls, including Biles. Simone Biles is one of the greatest athletes of all time. She's won six all-around world championships and eleven Olympic medals (seven gold). Five gymnastics moves are named after her, she received the Presidential Medal of Freedom (the youngest recipient ever), and at an age when most elite gymnasts have retired, Biles is not just still competing--she's dominating. She's soaring in Paris this summer, bringing home more Olympic gold. She's having so much fun that LA 2028 is not out of the question. But when coach Aimee Boorman met her at a gym in Texas, Simone was just a seven-year-old kid. An exceptionally athletically gifted one, to be sure, but not yet great. That would take time, care, love, and balance. Boorman helped shape Biles, both pushing her and holding her back, protecting both her mental and physical health. "She's like a second mom to me," writes Biles, and Boorman was the National Team coach in 2016, where the US--and Biles--took home all-around gold. The Balance combines unprecedented insider perspective on a legend, newsworthy details on gymnastics history, and compelling lessons on coaching, leadership, and development"--